2020
DOI: 10.1073/pnas.1912505117
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic and pheromone-specific intrinsic polarization cues interfere with gradient sensing in Saccharomyces cerevisiae

Abstract: Polarity decisions are central to many processes, including mitosis and chemotropism. InSaccharomyces cerevisiae, budding and mating projection (MP) formation use an overlapping system of cortical landmarks that converges on the small G protein Cdc42. However, pheromone-gradient sensing must override the Rsr1-dependent internal polarity cues used for budding. Using this model system, we asked what happens when intrinsic and extrinsic spatial cues are not aligned. Is there competition, or collaboration? By live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…The observation that yeast cells are able to orient polarization toward artificial pheromone sources generated by micropipets (Nern and Arkowitz, 1998;Segall, 1993;Valtz et al, 1995) or microfluidic devices (Brett et al, 2012;Dyer et al, 2013;Hao et al, 2008;Hegemann et al, 2015;Jin et al, 2011;Kelley et al, 2015;Lee et al, 2012;Moore et al, 2008;Moore et al, 2013;Paliwal et al, 2007;Vasen et al, 2020) has focused attention on the mechanism whereby cells decode a stable gradient of pheromone. Although yeast cells are clearly capable of polarizing growth toward an exogenous pheromone source, wildtype cells failed to polarize growth toward partners that were secreting pheromone uniformly around their surface.…”
Section: Re-evaluating the Pheromone Landscape Of Mating Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…The observation that yeast cells are able to orient polarization toward artificial pheromone sources generated by micropipets (Nern and Arkowitz, 1998;Segall, 1993;Valtz et al, 1995) or microfluidic devices (Brett et al, 2012;Dyer et al, 2013;Hao et al, 2008;Hegemann et al, 2015;Jin et al, 2011;Kelley et al, 2015;Lee et al, 2012;Moore et al, 2008;Moore et al, 2013;Paliwal et al, 2007;Vasen et al, 2020) has focused attention on the mechanism whereby cells decode a stable gradient of pheromone. Although yeast cells are clearly capable of polarizing growth toward an exogenous pheromone source, wildtype cells failed to polarize growth toward partners that were secreting pheromone uniformly around their surface.…”
Section: Re-evaluating the Pheromone Landscape Of Mating Cellsmentioning
confidence: 99%
“…For successful mating, the pheromone landscape must be decoded to orient polarity toward the partner. However, imaging of polarity factors revealed that initial polarity sites were not always oriented toward the eventual mating partner in mating mixes (Henderson et al, 2019;Wang et al, 2019) or up the gradient in cells exposed to artificial pheromone gradients (Dyer et al, 2013;Hegemann et al, 2015;Jin et al, 2011;Kelley et al, 2015;Vasen et al, 2020). Rather, the location of the polarity site changed over time, stabilizing at better-oriented locations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These external and internal cues might oppose each other or synergize through mechanisms that are is still under study. We recently showed in the Cdc42-signaling system of the budding yeast S. cerevisiae, that intrinsic polarization cues actually interfere with mating pheromone gradient decoding, as yeast genetically modified to lack all known internal landmarks track external gradients better [1].…”
Section: Introductionmentioning
confidence: 99%
“…Our recent observations revealed that the mechanism of polarization in response to pheromone depends on cell-cycle position. In response to uniform external pheromone, cells in the G1 phase assemble de novo polarization patches and form their MPs directly at the site of the dominant distal internal landmark [1] (Figure 1a). In contrast, if cells are in the middle of a cell division (i.e., out of G1) at the time of stimulation, they first finish mitosis and then utilize the already assembled cytokinesis-related polarity patch at the bud-neck.…”
Section: Introductionmentioning
confidence: 99%